1995
DOI: 10.1177/1077727x95233002
|View full text |Cite
|
Sign up to set email alerts
|

Goal Setting and Control Orientation of Pregnant/Parenting Female Adolescents in the GRADS Program

Abstract: The Graduation, Reality, and Dual‐role Skills (GRADS) home economics program helps at‐risk pregnant/parenting teens graduate from high school, set life goals, and feel empowered. The major purpose of this research was to ascertain if female GRADS students differed from nonpregnant/nonparenting female teens on types of goals seen as most important, goal orientation, and locus of control. Comparisons were made among GRADS students in the program for 1 year or more, GRADS students new to the program, and a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…These perceptions are critical because the importance of achievable aspirations among pregnant and mothering teens has been clearly established (White and Cummings 1995;Werner and Smith 1992;Furstenber et al 1987;Furstenberg et al 1989;Leadbeater 1996). Present results add a new dimension to the educational support literature by directly examining the perceptions of pregnant and mothering adolescents.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These perceptions are critical because the importance of achievable aspirations among pregnant and mothering teens has been clearly established (White and Cummings 1995;Werner and Smith 1992;Furstenber et al 1987;Furstenberg et al 1989;Leadbeater 1996). Present results add a new dimension to the educational support literature by directly examining the perceptions of pregnant and mothering adolescents.…”
Section: Discussionmentioning
confidence: 97%
“…Although a causal relationship has not been established, girls' aspirations and goals for the future often go unfulfilled after having a baby (Barbour et al 1993). Not only do aspirations contribute to achievement levels among adolescent mothers, but also help to ease the transition into the parent role (White and Cummings 1995). Longitudinal studies have shown that aspirations and school support act as protective factors against the stressors adolescent mothers face (Werner and Smith 1992;Furstenberg et al 1987;Furstenberg et al 1989;Leadbeater 1996).…”
Section: Introductionmentioning
confidence: 96%
“…The quantitative studies tended to use a larger number of participants, to be nonexperimental, and to be primarily cross-sectional and comparative in design (e.g., Hansford & Drummond, 1992;Klaw & Rhodes, 1995). The data collection methods were typically interviews (e.g., White & Cummings, 1995) or focus groups (e.g., Blinn, 1990), with only one study not using some form of verbal communication with participants to gather data (Hansford & Drummond, 1992). Several researchers developed questionnaires to gather specific information of interest from participants (e.g., Klaw et al, 2003).…”
Section: Strengths Of Past Research Studiesmentioning
confidence: 99%
“…One third of the studies indicated that adolescent mothers' career development skills need further development (e.g., White & Cummings, 1995). For example, Ortiz and Bassoff (1987) found that 80% of participants identified career goals for their future but did not know how to achieve their goals.…”
Section: Areas Of Exploration For Future Researchmentioning
confidence: 99%
“…Pregnant and parenting young women are permitted to attend publ1c school and a vanety of programs des1gned espec1ally to support them have sprung up across Canada and the Un1ted States (Furstenberg 1976, MacN1der, 1998Pol1t & Kahn, 1987Ray & Roloff, 1994Roosa . 1986. Wh1te & Cumm1ngs 1995.…”
Section: Career Preparat1on Program Des1gnat1onmentioning
confidence: 99%